ANALISIS ANGGOTA PERPUSTAKAAN PADA DINAS ARSIP DAN PERPUSTAKAAN KOTA BANDUNG TAHUN 2015-2021 - Faizal Mohamad Taufiq; Didik Prata Wijaya; Mochamad Reinnal Rachman (Perpustakaan Nasional RI, 2022)
Since 2015 the manufacture of library membership cards at the Bandung City Disarpus has been computerized. The application used for making library membership cards is an integrated library system (inlislite) application. Until now, studies on the analysis of library members have not been widely discussed and published in scientific journals, especially those related to the Bandung city library. The purpose of this study is to determine the number of active members of the library; number of active members by gender; the type of active member of the library; active members of the library by occupation; and active members of the library by age group. Data on active members of the library at the Bandung City Archives and Library Service from 2015 to 2021 can be concluded that the total number of library members was 9,043 people. 2019 was the highest year for library membership cards manufactured, which were 2,734 people or 30.23%. Library members with female gender being the highest number, which were 6279 people or 69.43%. Based on the type of members, the general group was the highest in 2015-2021 with 4,145 people or 45.84%. Based on the type of work, the highest number of library members are students with 3,115 people or 34.45%. And based on the age group, the highest number of library members were the age of 12 to 25 years (teenagers) as many as 5,365 people or 59.33%. Librarians at Department Archives and Libraries of Bandung City are expected to maintain the quality of service performance, especially in making library membership cards, so that library user visits can continue to increase. Department Archives and Libraries of Bandung City is expected to improve the quality and quantity in the procurement of books, especially for the age group of teenagers aged 12 to 25 years.